The status of industrialization and development of exosomes as a drug delivery system: A review - Yi Yin; Xing Han; Cheng Li; Tonghui Sun; Kailin Li; Xionghao Liu; Mujun Liu (Frontiers Media S.A., 2022)
Exosomes, as natural biomolecular carriers produced by cells, have the potential and advantage of delivering drugs to target organs or cells in vivo. The steps to improve exosomes as a drug delivery system can be divided into three steps:large-scale preparation of exosomes, loading of drugs and targeted delivery of exosomes. Based on the existing production process and technology, there is still much room for improvement. This review highlights the research progress in three aspects and proposes new technologies and innovative approaches to improve the efficiency of exosome delivery.